Usability study on Sistem Pengurusan Komputer Bersepadu (SPKB) for Royal Malaysian Air Force (RMAF) / Nurul Ain Hassim - Hassim, Nurul Ain (2013)
One of the most vital characteristic of a system is its ability to access the ease of use of the system. However, most of the software developers only focus on developing the system but not concern about the usability of the system. In reality, the usability of the system is an important aspect of system development. Poor usability will effects the utility of the system and will wasted the user's time, causes worry and frustration and discourages further to use the system. Therefore, Integrated Computer Management System (SPKB - Sistem Pengurusan Komputer Bersepadu) is one of the Information and Communication Technology (ICT) project based on integrated logistics support concept (ILS) for asset management that developed for Royal Malaysian Air Force to support their supply chain management. This study is conducted to identify the usability factors that might affect on SPKB system routine. Using Nielsen Jakob Model of usability, the questionnaire is designed to evaluate the SPKB system. The questionnaire is based on five usability factors; efficiency, learnability, memorability, errors and satisfaction. The interview is conducted after analyzing the result from the questionnaire to identify and overcome the problem to enhance the SPKB system. Finally findings are presented to know the level of usability on SPKB system.